Anterpartum Eclampsia and Partial HELLP Syndrome in Multigravida at 38 Weeks of Pregnancy: Case Report: Eklampsia Antepartum dan Partial HELLP Syndrome pada Multigravida Usia Kehamilan 38 Minggu: Laporan Kasus - Catherine, Agatha; Zulfadli, Zulfadli (CV. Jasa Sukses Abadi, 2025)
Eclampsia defined as the occurrence of seizures in women whom meet the criteria for preeclampsia. The effects of preeclampsia that progress to eclampsia will cause neurological symptoms, including seizures, cerebral circulation dysregulation and neuropathology. Signs and symptoms of eclampsia include seizures, severe agitation and altered of consciousness. Preeclampsia and eclampsia are the causes of the high level of maternal mortality in the world. A 38 years old woman came to emergency room at RSUD Dr H Abdul Moeloek because of convulsion 1 hour ago which lasted about 5 minutes. Patients complain of blurred vision, nausea and vomiting. Patient founded hypertension was 174/110 mmHg and pretibial edema. Obstetric examination shows the pelvic inlet has not yet entered, his cannot be palpable, vaginal toucher found a soft portion without opening, amniotic and presentation cannot be assessed. Laboratory examination shows Hb 11.6 gr/dl, leukocytosis 19,700/µL, increased liver function SGOT 40 U/L, increased lactate dehydrogenase (LDH) 655 U/L and proteinuria 500 mg/dL. Management in the ER consists of observation, administration of conservative and abortive therapy to stop seizures. MgSO4 injection was given at slow bolus dose of 4 grams followed by 500 ml RL infusion mixed with 6 grams of MgSO4 used up for 6 hours. Corticosteroid administration in this case was represented by an injection of Dexamethasone 10 grams every 12 hours. Nifedipine was given at 3x10 mg and Methyldopa at 3x500 mg. Keywords : Eclampsia, Partial HELLP Syndrome, Conservative Management, Antihypertensive Agent.